1987
DOI: 10.1128/jvi.61.6.1808-1813.1987
|View full text |Cite
|
Sign up to set email alerts
|

Multiple integration site of hepatitis B virus DNA in hepatocellular carcinoma and chronic active hepatitis tissues from children

Abstract: Attention was directed to hepatitis B virus (HBV) integration in tissues obtained from an hepatocellular carcinoma (HCC) of an 11-year-old boy and from the liver of his 6-year-old brother, who had chronic active hepatitis. Multiple HBV DNA integration sites were demonstrated in both tissues. Cell population(s) in the HCC and liver from the patient with chronic active heptaitis were assumed to be heterogeneous with regard to HBV integration. The integrated forms in the two tissues showed similar genetic organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 28 publications
5
48
0
Order By: Relevance
“…The result that 90% of the IPCR products belonged to type I integrants is different from the statistical data for adult HCC, in which the percentage of type I integrants was estimated at 25% [Robinson, 1992]. Yaginuma et al [1987] have studied one childhood HCC tissue and found that at least one viral end of each HBV integrant was restricted to the DR1 region. We suggest that the DR1 region is the preferred viral junction for HBV integration in childhood HCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result that 90% of the IPCR products belonged to type I integrants is different from the statistical data for adult HCC, in which the percentage of type I integrants was estimated at 25% [Robinson, 1992]. Yaginuma et al [1987] have studied one childhood HCC tissue and found that at least one viral end of each HBV integrant was restricted to the DR1 region. We suggest that the DR1 region is the preferred viral junction for HBV integration in childhood HCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Further characterization of the oncogenic potential and the interaction partners of RBMY protein in liver cells may help clarifying its function in liver cells. Giacchino et al, 1987 8 Single (4) Southern blotting Chang et al, 1991 Multiple (1) Negative (3) 1 Multiple (1) Molecular cloning and sequencing Yaginuma et al, 1987…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to study the status of HBV DNA integration in childhood HCCs. Hepatitis B surface antigen (HB-sAg) has been detected in 100% of children with HCC in Taiwan [Hsu et al, 19871, most are infected with HBV perinatally from their mothers [Chang et al, 19891. Integration of HBV DNA in childhood HCCs has also been reported [Yaginuma et al, 1987;Chang et al, 19911. Chang et al [19911 have demonstrated that integration of HBV DNA at a single site is more common in childhood HCC tissues than in adult HCCs.…”
Section: Introductionmentioning
confidence: 78%
“…Integrated hepadnavirus DNA is very frequently incomplete and rearranged (10,11,13,34), and a deletion in the C gene region has often been observed (20,21,35,36), a possible result of a site-specific integration of the viral DNA at the direct repeats (16,17,37,38), which are located 5' of the C gene open reading frame. Transcription and expression of viral genes from integrated hepadnavirus DNA may also play a role in tumorigenesis.…”
Section: Although the Role Of Chronic Hepadnavirus Infection In Tumormentioning
confidence: 99%
“…Chronic WHV infection in woodchucks is frequently associated with hepatocellular carcinoma (HCC) (2-6), so this animal is a good model for studying the relationship between chronic hepadnavirus infection and HCC development. Whereas replication of hepadnaviruses (7-9) and integration of viral DNA in tumor cells has been studied extensively (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), transcription of WHV and HBV DNA in tumor tissue has received less attention. Moroy et al (20,21) studied transcription of WHV DNA in chronically infected liver and found two major transcripts of 3.7 and 2.1 kilobases (kb) length; in three tumors they found transcripts of different size.…”
mentioning
confidence: 99%